The Motivating Operation and Negatively Reinforced Problem Behavior: A Systematic Review. (January 2014) - Langthorne, Paul; McGill, Peter; Oliver, Chris
The concept of motivational operations exerts an increasing influence on the understanding and assessment of problem behavior in people with intellectual and developmental disability. In this systematic review of 59 methodologically robust studies of the influence of motivational operations in negative reinforcement paradigms in this population, we identify themes related to situational and biological variables that have implications for assessment, intervention, and further research. There is now good evidence that motivational operations of differing origins influence negatively reinforced problem behavior, and that these might be subject to manipulation to facilitate favorable outcomes. There is also good evidence that some biological variables warrant consideration in assessment procedures as they predispose the person's behavior to be influenced by specific motivational operations. The implications for assessment and intervention are made explicit with reference to variables that are open to manipulation or that require further research and conceptualization within causal models.